2018
DOI: 10.1136/bmjopen-2017-020039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, consequences and prevention of falls in institutionalised older adults in the province of Malaga (Spain): a prospective, cohort, multicentre study

Abstract: ObjectivesFalls are an important adverse event among institutionalised persons. It is in this clinical setting where falls occur more frequently than in any other, despite the measures commonly taken to prevent them. This study aimed to determine the characteristics of a typical institutionalised elderly patient who suffers a fall and to describe the physical harms resulting from this event. We then examined the association between falls and the preventive measures used.MethodsThis was a prospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 13 publications
(13 reference statements)
2
17
0
2
Order By: Relevance
“…Cognitive impairment, severe mobility problems and a greatly restricted capacity to perform daily living activities are determining factors in the decision to implement restraint systems. 2,7 Each nursing home has specific needs determined by elderly characteristics, number of residents, knowledge and experience, prevention practice, fall recording and reporting, and the location and architectural characteristics of buildings, 4 which can influence post-fall practices and behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive impairment, severe mobility problems and a greatly restricted capacity to perform daily living activities are determining factors in the decision to implement restraint systems. 2,7 Each nursing home has specific needs determined by elderly characteristics, number of residents, knowledge and experience, prevention practice, fall recording and reporting, and the location and architectural characteristics of buildings, 4 which can influence post-fall practices and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Falls are considered the main cause of restrictions in activities of daily living for this age group, especially among individuals with cognitive decline, for whom it is a significant contributory factor to their dependence. 1,2 Although this in itself is cause for concern, the problem is compounded by significant post-fall consequences like fear and post-fall anxiety syndrome, which translate into a loss of self-confidence and the self-imposition of limitations both at home and within institutions. 1 The relationship between falls and the institutionalized elderly is complex due to its direction -whether falls are the only cause or just one factor in deciding whether to admit an elderly person to a nursing home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every fifth fall causes serious injuries, including hip fractures or head trauma [6]. Falls in the world rank second, after road accidents, among the causes of death caused by accidental injuries [7]. Other studies among older people living in a home environment have found an even higher percentage of people who fall within a year, reaching 30-40%.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…These events are even more frequent in long-term care facilities for older adults, where approximately half of the institutionalised residents suffer at least one fall per year (Rubenstein and Josephson, 2002; Panel on Prevention of Falls in Older Persons (American Geriatrics Society and British Geriatrics Society), 2011). Along with physical exercise, the main preventive measure in nursing homes is the use of bedrails and the application of physical restraints (Aranda-Gallardo et al ., 2018). However, the prolonged use of such devices may reduce the residents’ functional capacity, since limited mobility has physical consequences.…”
Section: Introductionmentioning
confidence: 99%